Living on the Margins Beyond Gender Binaries: What are the Challenges to Securing Rights. (2nd November 2021) - Darling, Marsha J. Tyson
Abstract : This article identifies the extent to which deeply embedded ideas and beliefs about the innate normalcy of the man/woman gender binary feed longstanding attitudes against those persons whose gender identity is believed to be aberrant and pathological. The discrimination directed at LGBTQ + persons creates inequities that deepen their social marginalization and push them further away from the exercise of constitutional rights. This article urges public administration to create effective interventions to eliminate the racism and gender-identity hate and discrimination that continue to place an unfair burden on especially LGBTQ+ Black, Indigenous and other Persons of Color (BIPOC).